Никита Шаповал: мировоззренческие основы Социологической теории - Юренко, А. (Социология: теория, методы, маркетинг, 2001)
The article deals with sociological and philosophical ideas of M.Shapoval (1882-1932), one of the founders of Ukrainian sociology. The author presents the main scientific ideas of M.Shapovalís works, including his manuscripts, mostly unknown even to specialists.Comparative analyses of these materials make it possible to conclude about a significant contribution made by M.Shapoval into the positivist approach to social sciences and creative application of the newest sociological concepts of his time.